PENINGKATAN NILAI JUAL IKAN ASIN DI PULAU RENI, DISTRIK KEPULAUAN AYAU, KABUPATEN RAJA AMPAT, PAPUA BARAT: THE INCREASING SALE VALUE OF SALTED FISH IN RENI ISLAND, AYAU ISLANDS DISTRICT, RAJA AMPAT DISTRICT, WEST PAPUA - Asthervina Widyastami Puspitasari; Agung Setia Abadi; Kadarusman Kadarusman; Mustamir Kamaruddin; Marcelinus Petrus Saptono; Charliany Hetharia; Ivonne M. Leiwakabessy; Nasrul Fauzi; Ilham Marasabessy; Ratna Ratna; Luluk Suryani; Roger R. Tabalessy; Ernawati Ernawati (Buletin SWIMP, 2023)
Lack of technical knowledge about salted fish packaging causes the selling price of salted fish on Reni Island to be low. Salted fish is a flagship product in Reni Island. This aims of this program to provide additional knowledge and skills for the community, especially housewives on Reni Island regarding the handling and packaging of salted fish. This activity was held on October 14, 2021 on the coast of Reni, Ayau Islands, Raja Ampat Regency, West Papua Province in collaboration between 10 (ten) universities in the Sorong Raya area (DIKTISORAYA Forum). The methods used include lectures, training, and discussions. Procedures for handling and packaging salted fish include: sorting fish by type and size; weighing; labeling and packaging. Salted fish handling and packaging activities run smoothly, efficiently and effectively. The suggestions for community service that should be done on Reni Island are offline and online marketing training and microeconomic management as a trigger for improving the welfare of the people of Reni Island.